Millennial generation's Islamic banking behavioral intention: The moderating role of profit-loss sharing, perceived financial risk, knowledge of Riba, and marketing relationship - Asyari; Mohammad Enamul Hoque; M. Kabir Hassan; Perengki Susanto; Taslima Jannat; Abdullah Al Mamun (Journal of Risk and Financial Management, 2022)
Despite tons of studies on Islamic banking (IB) behavior, there is a lack of understanding of the Millennial generation's attitude to and subjective norms surrounding Islamic banking, as well as of their behavioral intention toward Islamic banking. Therefore, the present study investigates the influence of the Millennial generation's attitude and subjective norms on their behavioral intention toward Islamic banking products and services. This study also focuses on the moderating roles of profit-loss sharing, perceived financial risk, knowledge of riba, and relationship marketing on the nexus of antecedent and behavioral intent of Islamic banking. This study has developed a conceptual framework, employed a questionnaire to collect data for understudying relationships, and constructed a predictive model. Within the proposed conceptual framework, structural equation modeling is employed to investigate the extent and direction of the link. We discovered that Millennial generation consumers' attitudes and subjective norms influence and predict their behavioral intention towards Islamic banking. With the exception of perceived financial risk, all moderators have direct effects on behavior intention toward Islamic banking and could be antecedents of behavior intention toward Islamic banking. Profit-and-loss sharing and knowledge of riba moderate the nexus of attitude and behavioral intention and the nexus of subject norms and behavioral intention. Our findings thus extend the literature on Islamic banking and consumer behavior context.
Keywords: 650; Islamic banking; behavioral intention; Muslim Millennial